Bilious Vomiting in the Newborn: A Three-Year Experience in a Tertiary Medical and Surgical Centre - Rebecca A Lee; Theodore Dassios; Ravindra Bhat; Anne Greenough (Case Reports in Pediatrics)
Background. Bilious vomiting in the newborn is common and requires urgent attention to exclude malrotation. The proportion of neonates with surgical abnormalities, however, is small, and there are other causes. Study Objectives. We reviewed our experience of infants with bilious vomiting to demonstrate the importance of input from the tertiary surgical and medical team to arrive at the correct diagnosis. Design. Admissions with bilious vomiting/aspirates of term born infants over a three-year period to a tertiary medical and surgical unit were reviewed. Results. During the study period, 48 infants were admitted with bilious vomiting. Forty-five infants had upper gastrointestinal (UGI) contrast studies, and only six had an abnormal study: four had malrotation and two had Hirschsprung’s disease. Of the infants with a normal UGI study, no cause was identified in 20 cases, 13 infants were treated for sepsis, one had a meconium plug, one an ovarian cyst, and two infants were polycythaemic. One infant was diagnosed with bilateral polymicrogyria (PMG) on brain MRI and another was found to have hypochondroplasia FGFR3 skeletal dysplasia. Conclusion. Neonates with bilious vomiting may have a variety of underlying diagnoses and need to be referred to a tertiary surgical and medical centre to ensure appropriate diagnosis is made.